Plan de responsabilidad social empresarial basado en norma ISO 26000 como ventaja competitiva en la Cooperativa de Transportes “Reina del Camino” - Barberán Macías, Jorge Luis (2025)
The objective of this research was to propose a Corporate Social Responsibility (CSR) plan based on the ISO 26000 standard to enhance the competitive advantage of the "Reina del Camino" Transport Cooperative in Chone canton, emphasizing its significant contribution to the country's commercial and productive growth. Given that this sector plays a crucial role in economic and social development, raising awareness about integrating CSR activities into business operations is essential. The research followed a qualitative and quantitative approach, relying on high-impact studies and applying inductive, deductive, and analytical-synthetic methods. A survey was used as an evaluation instrument, validated by a panel of experts and applied to 100 cooperative members. The results highlighted a lack of knowledge regarding CSR and sustainability within the organization's strategic plan, mission, vision, and objectives. Additionally, the study identified the need to respect the interests of all stakeholders involved with the cooperative. Based on these findings, it is concluded that formalizing the application of CSR principles is necessary to improve the organization's reputation and generate a long-term competitive advantage.